Empire's Nursery : Children's Literature and the Origins of the American Century - Rouleau, Brian (Book collections on Project MUSE., 2021)
"America's empire was not made by adults only. In fact, junior citizens were essential to its creation. Children's literature during the nineteenth and twentieth centuries sought to impart an imperial consciousness among the nation's youth, while adult authors strive to raise rising generations of enthusiastic juvenile jingoes. But young people were neither unwitting nor unwilling puppets in the propagation of America's expansionistic foreign policy. Instead, Empire's Nursery demonstrates that juvenile readers often played an active part in committing the country to adventurism overseas. The history of the United States in the world must therefore make room for the country's littlest policymakers. As kids eagerly read dime novels, series fiction, pulp magazines, and comic books that dramatized the virtues of empire, they helped entrench a growing belief in America's indispensability to the international order. The American Century's actualization depended upon the patient work of writers proselytizing among the youthful millions educated to embrace their Uncle Sam's growing global entanglements"--